“A gente precisa ter um olhar mais atento, porque é a nossa escola, né? [...] e quem tem o conhecimento somos nós”: currículo e práticas educativas no Ensino Médio da Escola Pataxó de Barra Velha (BA) - Danielle Alves Martins (2022)
The main aim of this doctoral research is to understand the educational practices that ground the curriculum of the Pataxó Indigenous High School in Barra Velha, Bahia, Brazil. It is situated amidst intercultural education and curriculum studies, aligned with the so-called critical pedagogy, broadened by the studies under the umbrella of decolonization. The participants are Indigenous Pataxó teachers from Barra Velha and students of Fiei-Matemática undergraduate course from the same territory. It is a qualitative research seeking to research with the Indigenous and not only about them, in a research engaged with the fights of Pataxó people. The empirical material was mainly collected virtually, mediated by digital technology, due to the Covid-19 pandemic, using platforms of video conference, online apps (WhatsApp, Facebook), and email. The material entails virtual meetings to create the curriculum; virtual participation in Fiei outreach projects and classes; and online interviews and messages. To produce and record research material, we used: field notes, video recording, and semi structured interviews. In light of the theoretical approaches, we analyzed the educational practices that ground the curriculum of Pataxó High School in Barra Velha, including those experienced in the community, when the school space was closed due to the pandemic, and the relation of these practices with pre-service Pataxó teachers in Fiei. We have seen that Fiei allowed Pataxó teachers to have formative experiences that made them not only assume the role of high school teachers, but also enact knowledge based on a better understanding of intercultural education. One of these strategies was the methodology of Sociocultural Calendar which allows the description of educational practices in the territory during different times of Pataxó life and which are relevant to this people, permeating the relation of Pataxó community with the everyday life, nature, land, sea, and the moon. These practices express Pataxó ancestry, while enabling Indigenous teachers to seek an articulation between traditional Indigenous world and Western scientific/school world. In this sense, Fiei opened space for teachers to practice their culture, which has probably contributed to revitalize the Full Moon Ritual in the community via school, based on the work with the Calendar. The analysis of the curriculum creation has also shown that the education practice guiding the pedagogical work in high school is the Full Moon Ritual, the central axis of structured practices through the Sociocultural Calendar, establishing an intercultural curriculum. The curriculum creation is marked by colonialism, from the relations established between the different rationalities in dispute: the Western logic of education – neoliberal capitalism – versus the ancestral education. Therefore, we can affirm that we cannot create a curriculum, even if intercultural, without considering the tensions and continuation of subalternities. At the same time, we concluded that understanding Pataxó educational practices is also understanding how to produce an intercultural curriculum established in a space of fights to guarantee an Indigenous school anchored on community values, that is, Indigenous, specific, distinguished, and intercultural.